Animals in Dutch Travel Writing, 1800-present - Honings, Rick; Op De Beek, Esther (Leiden University Press, 2023)
Apart from humans, animals play a pivotal role in travel literature. However, the way they are represented in texts can vary from living companions to metaphorical entities. Existing studies mainly focus on the representation of conventional or unconventional roles that are assigned to animals from around the Napoleonic age until now, roles that have been subject to change and that tell us a lot about human reflections on encounters with non-human creatures and the position of man in this rapidly changing world. In this edited volume, scholars from the Netherlands and abroad analyse the roles that animals play in Dutch travel literature from 1800 to the present. In this way, we aim to provide new insights into the relationships between man and animals, in textual expressions and real life, and to add the 'Dutch case' to the flourishing international field of travel writing studies.